Living in the environment - Miller, G. Tyler (George Tyler), 1931-; Spoolman, Scott (Belmont, CA : Brooks/Cole Cengage Learning, 2012)
This volume has a balanced approach to environmental science instruction, with bias-free comparative diagrams throughout and a focus on prevention of and solutions to environmental problems.
Previous ed.: 2009.
Copyright date given as 2012, book received in 2011.
Includes index.
Keywords: Environmental sciences; Human ecology; Environmental policy; Pollution; Sustainable development